A review of strategic deployment of peacekeeping forces as an effective measure of preventing escalation of violence - Piyasiri, I.D (My University, 2009)
There have been many inter-state and intra-state armed conflicts fought by human beings I the world. Even.today, there are internal armed conflicts in many countries. All these pnflicts have caused many hardships on human beings. Therefore, these conflicts are destructive for parties involved in the conflict and world community at large. All these conflicts are man-made. Therefore, if all parties to a conflict think rationally, hould weigh the pros and cons of a conflict in order to prevent conflicts and to make peace. In lis process, both state and non state actors hold the responsibility of preventing violence and naking peace. There are various causes that motivate human beings. These motivations are the seeds lat germinate causes of conflicts. Therefore, if the political commitment of preventing violence nd making peace' is genuine, the military personnel and other stakeholders should possess bquired competencies to perform tasks in peacekeeping operations. Peacekeeping operations can be viewed as a system. The success of peacekeeping rstem depends on functions of various other sub-systems. During peacekeeping operations the ansformation of actors that contribute towards the formation of conflict is of pivotal lportance. In this process of transformation, the use of force is not the effective tool. IX